Fear of new or recurrent melanoma after treatment for localised melanoma. Issue 11 (2nd February 2017) - Bell, Katy J.L.; Mehta, Yachna; Turner, Robin M.; Morton, Rachael L.; Dieng, Mbathio; Saw, Robyn; Guitera, Pascale; McCaffery, Kirsten; Low, Donald; Low, Cynthia; Jenkins, Marisa; Irwig, Les; et al.
Abstract: Objective: To estimate the amount of fear of new or recurrent melanoma among people treated for localised melanoma in an Australian specialist centre. Methods: We randomly selected 400 potential participants from all those treated for localised melanoma at the Melanoma Institute Australia during 2014 ( n = 902). They were asked to complete an adapted version of the Fear of Cancer Recurrence Inventory (FCRI). We calculated summary statistics for demographics, clinical variables and total FCRI and subscale scores. Results: Two hundred fifteen people (54%) completed the FCRI questionnaire. The overall mean severity subscale score was 15.0 (95% CI 14.0‐16.1). A high proportion of participants had scores above a proposed threshold to screen for clinical fear of cancer recurrence (77% and 63% of participants with and without new or recurrent melanoma had severity subscale scores ≥13). Most participants also had scores above a threshold found to have high specificity for clinical fear of cancer recurrence (65% and 48% of participants with and without new or recurrent melanoma had severity subscale scores ≥16). The severity subscale appeared to discriminate well between groups with differing levels of risk of new or recurrent melanoma. Conclusions: There is a substantial amount of fear of new or recurrent melanoma among this population, despite most having a very good prognosis.